KETERAMPILAN MENULIS LAPORAN PENGAMATAN SISWA KELAS V SD MELALUI MODEL EXAMPLES NON EXAMPLES - Dewi, Titi Purnama; Rahayu, Galih Dani Septiyan (COLLASE (Creative of Learning Students Elementary Education), 2021)
This study is entitled to improve the skills of writing observational reports of fifth-grade elementary school students through the Examples Non-Examples Model, this title is motivated by consideration of the lack of student skills when writing reports based on learning objectives, material criteria, and characteristics of fifth-grade elementary school students. The purpose of this research is to find out the improvement in the skills of fifth-grade elementary school students in writing observation reports through the Examples Non-Examples Model in elementary schools. The study conducted a qualitative approach by observing and evaluating in the form of non-test techniques using questionnaires and observation sheets. This research will focus on "Improving the Skill of Writing Reports on Observation of Grade V Elementary Students through the Examples Non-Examples Model " whose main objective is grade V students at SDN 037 Sabang, Bandung. Based on the results of data analysis and discussion of research results that among the characteristics of students who have low observing and writing skills, using the Examples Non-Examples Model learning model are interconnected so that it affects the writing skills of the fifth-grade students' observation reports at SDN 037 Sabang, Bandung. Thus, the use of appropriate learning models can achieve the expected learning objectives. In this case, examples non-examples is one of the learning models that can improve the writing skills of students' observation reports.Â